Free-Form and Deformable Energy Storage as a Forerunner to Next-Generation Smart Electronics - Kwak, Soyul (Micromachines (Basel), 2020)
Planar and rigid conventional electronics are intrinsically incompatible with curvilinear and deformable devices. The recent development of organic and inorganic flexible and stretchable electronics enables the production of various applications, such as soft robots, flexible displays, wearable electronics, electronic skins, bendable phones, and implantable medical devices. To power these devices, persistent efforts have thus been expended to develop a flexible energy storage system that can be ideally deformed while maintaining its electrochemical performance. In this review, the enabling technologies of the electrochemical and mechanical performances of flexible devices are summarized. The investigations demonstrate the improvement of electrochemical performance via the adoption of new materials and alternative reactions. Moreover, the strategies used to develop novel materials and distinct design configurations are introduced in the following sections.